Daughter of the East: A Sisyphean Attempt of Benazir Bhutto in Politicizing Individual Distress for Collective Trauma - Lamichhane, Yog Raj (English Language Teaching Perspectives, 2022)
The paper explores the efforts of Benazir Bhutto in politicizing her individual distress for cultural trauma in her autobiography The Daughter of the East. It mainly examines how her multiple efforts of transferring personal trauma into social trauma turn out to be Sisyphean attempts. Generally, a never-ending futile endeavour that never gets completed is understood as the Sisyphean attempt. Hence, the paper illustrates the same endless and futile side of Bhutto’s exertions in developing cultural trauma through her life writing. Actually, her father Zulfiqar Ali Bhutto, the former Pakistani Prime Minister, was assassinated by the military regime in 1979. On the foundation of the assassination, she became Prime Minister of Pakistan twice. Moreover, that tragic event also provided the major content for the writing of this autobiography. In this context, in this qualitative study of the autobiography, the major insights on the social process of cultural trauma as initiated by Jeffrey C. Alexander are used as the theoretical framework to evaluate the relevant textual evidence. Moreover, the concepts of Sidonie Smith and Julia Watson concerning the culture of writing autobiographies are also borrowed to support the argument. Ultimately, the textual analysis mainly signals that censored media, extreme judiciary and forceful martial law including the government-endorsed faith of Pakistan seem to hinder the social process of cultural trauma.